2008
DOI: 10.1111/j.1365-2141.2008.07360.x
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin with low dose dexamethasone and thalidomide is effective therapy in relapsed/refractory myeloma

Abstract: SummaryA combination of clarithromycin, low dose of thalidomide and low dose dexamethasone was used in a phase II study to treat patients with relapsed and refractory myeloma. Thirty patients received clarithromycin 250 mg twice daily and thalidomide 50 mg at night on an ongoing basis with 4-d pulses of 10 mg dexamethasone given monthly. Eight patients had permitted escalation of thalidomide dosage up to 200 mg daily. The combination was well tolerated and could be given to elderly, infirm and severely cytopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
1
10
0
2
Order By: Relevance
“…The putative efficacy was buttressed by a recent report where the same combination of drugs was used: however the dexamethasone was used in high-dose. Results were almost comparable with BLT-D (16). …”
Section: Introductionsupporting
confidence: 54%
“…The putative efficacy was buttressed by a recent report where the same combination of drugs was used: however the dexamethasone was used in high-dose. Results were almost comparable with BLT-D (16). …”
Section: Introductionsupporting
confidence: 54%
“…Based on observation that in PCL the response to standard therapy is extremely poor and the use of thalidomide in advanced MM has resulted in marked responses even in patients with advanced diseases, including those who relapsed after high-dose chemotherapy [69][70][71][72], some authors have used this promising drug also in patients with PCL [73,74]. Wohrer et al [75] reported the use of thalidomide in a patient with PPCL as a first line therapy achieving a very good partial response rapidly.…”
Section: Thalidomidementioning
confidence: 97%
“…According to Niesvizky et al the addition of CAM would allow a lower dose of dexamethasone while maintaining a high response rate. Indeed, Morris et al reported an overall response rate of 96%, of which 89% had at least 50% reduction in paraprotein, in relapsed and refractory myeloma patients when they received CAM combined with low dose dexamethasone and low dose thalidomide [38]. …”
Section: Human Datamentioning
confidence: 99%
“…Such combinations have been used in more than ten different trials [33–35, 37, 38, 40, 41, 44, 47, 91–93]. As such, CAM augments the response to dexamethasone when given alone or in combination with thalidomide to patients with MM [37, 94].…”
Section: Mechanism Of Actionmentioning
confidence: 99%